MEASUREMENT WORDS IN RELATED LANGUAGE LASALIMU AND KAMARU - Yohanis Sanjoko (Balai Bahasa Jawa Barat, 2015)
THIS article reviews measurement words in related language Lasalimu and Kamaru.Measurement word is a word following numeral and altogether create a phrase,namely numeral phrase and probably situated before a noun. The objective ofthis work is to describe the forms and classifications of measurement words inrelated language of Lasalimu and Kamaru. It used three stages of descriptivemethod, namely collecting, analyzing, and describing the data. The analysis usedshared method, namely immediate shared component. The result was the formand classification of measurement word in related language of Lasalimu andKamaru, namely (1) measurement word of animal, (2) measurement word of things,and (3) measurement word of human being. Each of them was divided into generalmeasurement word and particular measurement word.